PHARMACEUTICAL FORMS BASED ON CHELIDONIUM MAJUS L - Olimpia Dumitriu Buzia; Ion Gianina Mihaela; Earar Kamel; Tiutiuca Carmen; Batir Marin Denisa; Zetu Irina; Debita Mihaela; Stoian Valerian Ionut; Mardare Nela (Romanian Society of Oral Rehabilitation, 2022)
Given the abundant amount of hollyhock in the environment, given the special propertiesof the plant, used both internally, in hepato-biliary disorders and externally in various dermatological diseases, we set out to achieve a physical-chemicaland technological study. of this plant We obtained a soft extract from the plant Chelidonium majus L., which we dosed by the volumetric method, in order to determine the quantitative chelidonine From the soft extract of Chelidonium majus L, we made 4 ointments with different concentrations in the active substance; we determined the organoleptic properties, the pH, the display capacity, the stability in time of the ointments at different temperatures. The obtained results justified us to affirm the important role of this plant in the topical treatments of various dermatological diseases.